An OpenCL-Compliant Multi-core Platform and Its Companion Compiler - Nepomuceno, Ramon S.; Santos, Jonatas C.; Luz, Laysson O.; Silva, Ivan S. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
Nowadays, multi-core architectures have become mainstream in the microprocessor industry. However, while the number of cores integrated in a single chip growth, more important becomes the need for an adequate programming model. In recent years, the OpenCL programming model has attracted the attention of multi-core designers' community. This paper presents an OpenCL-compliant architecture and demonstrates that such programming model can be successfully used as programming model for general-purpose multi-core architectures.